Persepsi Terapis Wicara dalam Penggunaan Komunikasi Augmentatif Alternatif (KAA) untuk Pasien Afasia di Surakarta - Ghazy Maulana Khairy; R. Asto Soesyasmoro; Roy Romey Daulas Mangunsong (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Services for stroke patients with language impairment are growing. There are 30 speech therapists who are members of IKTWI DPC Surakarta working in speech therapy services for aphasia patients in Surakarta. Objectives: This study aims to determine the perception of speech therapists regarding the use of AAC in the selection of therapy methods for aphasia patients in Surakarta. Methods: Quantitative descriptive research design using purposive sampling totalling 30 speech therapists. Data collection through questionnaires using google form media and analysed descriptively and univariately to find out the description of speech therapy perceptions. Results: There were 30 speech therapists who became respondents from 289 active speech therapists in Surakarta, the perception of speech therapists about AAC knowledge (86.56%), the perception of speech therapy about the benefits of AAC in aphasia patients in Surakarta (74.2%), the perception of speech therapists about the role of speech therapists in the use of AAC in aphasia patients in Surakarta (77.36%), the perception of speech therapists about the obstacles to the application of AAC in Surakarta (74.5%). Conclusion: Most speech therapists in Surakarta believe that AAC can help in the intervention process of aphasia patients. However, there are difficulties in the availability of working field books to access, making it difficult for speech therapists to gain knowledge about effective evidence-based approaches in using AAC. Keywords: AAC, Aphasia, Perception, Speech Therapy.